2010
DOI: 10.1007/s10236-010-0365-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the spatial and temporal variability of dissolved organic matter in Liverpool Bay using excitation–emission matrix fluorescence and parallel factor analysis

Abstract: The spatial and diurnal tidal variability of dissolved organic carbon (DOC) concentrations and the composition of dissolved organic matter (DOM), as evaluated by high-temperature catalytic oxidation and excitation-emission matrix combined with parallel factor analysis (EEM-PARAFAC), respectively, were determined in Liverpool Bay. EEM-PARAFAC modeling resulted in six fluorescent components characterized as terrestrial humic-like (two), microbial humic-like (two), and proteinlike (two). The spatial distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 43 publications
10
78
1
Order By: Relevance
“…Indeed, component C1 has been reported as a ubiquitous FDOM component derived from the microbial degradation of phytoplankton by-products (Nagata, 2000;Stedmon and Markager, 2005;Zhang et al, 2009), as well as originating from specific Arctic terrestrial sources at low salinity (Walker et al, 2009) and various coastal and estuarine environments reported in Japan (Yamashita et al, 2008), the southeastern USA coast (Kowalczuk et al, 2009), in Liverpool Bay (Yamashita et al, 2011), and in Hudson Bay (Guéguen et al, 2011). Component 2 (C2) has been previously associated with high molecular weight and aromatic terrestrial organic matter (Stedmon et al, 2003;Walker et al (2009).…”
Section: Fluorescent Dommentioning
confidence: 99%
“…Indeed, component C1 has been reported as a ubiquitous FDOM component derived from the microbial degradation of phytoplankton by-products (Nagata, 2000;Stedmon and Markager, 2005;Zhang et al, 2009), as well as originating from specific Arctic terrestrial sources at low salinity (Walker et al, 2009) and various coastal and estuarine environments reported in Japan (Yamashita et al, 2008), the southeastern USA coast (Kowalczuk et al, 2009), in Liverpool Bay (Yamashita et al, 2011), and in Hudson Bay (Guéguen et al, 2011). Component 2 (C2) has been previously associated with high molecular weight and aromatic terrestrial organic matter (Stedmon et al, 2003;Walker et al (2009).…”
Section: Fluorescent Dommentioning
confidence: 99%
“…After the water samples reached room temperature, EEM fluorescence was measured according to Yamashita et al (2011). Briefly, emission scans from 290 to 600 nm at 2-nm intervals were acquired at excitation wavelengths between 250 and 450 nm at 5-nm intervals.…”
Section: Eem-parafac Analysismentioning
confidence: 99%
“…Unlike the common exponential decay patterns observed for C7 for the biomass leachates, C8 showed in most cases a combination of decreases and increases throughout the degradation process, suggesting that competing degradation and generation processes control the abundance of this component in the environment. Similar suggestions have previously been reported in the literature based on field data (Yamashita et al, 2008b(Yamashita et al, , 2010b) and C8 may in fact have a net accumulation in the environment after photo-or bio-degradation of DOM. As such it seems to justify its location on the PCA plot shown in figure 3.4.…”
Section: Quantitative Assessment Of Dom Photo-and Bio-reactivitysupporting
confidence: 88%